2011
DOI: 10.1111/j.1753-6405.2011.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of national mortality codes in identifying adjudicated cardiovascular deaths

Abstract: Objective: This study investigated the sensitivity and specificity of the national mortality codes in identifying cardiovascular disease (CVD) deaths and documents methods of verification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…It is most likely that this reflects an increasing awareness among doctors that diabetes is a key etiological factor in the development of CVD. Our findings are supported by a study by Harriss et al (26), which adjudicated 750 deaths from an Australian longitudinal cohort and found that of 54 deaths with an underlying ICD code listed as "diabetes," almost 60% were primarily due to CVD. Our somewhat lower estimates are most likely explained by our conservative approach, whereby only those diabetes cases that were "diabetes with circulatory complication" or "uncomplicated diabetes" were recoded.…”
Section: Comparison With the Literaturesupporting
confidence: 88%
“…It is most likely that this reflects an increasing awareness among doctors that diabetes is a key etiological factor in the development of CVD. Our findings are supported by a study by Harriss et al (26), which adjudicated 750 deaths from an Australian longitudinal cohort and found that of 54 deaths with an underlying ICD code listed as "diabetes," almost 60% were primarily due to CVD. Our somewhat lower estimates are most likely explained by our conservative approach, whereby only those diabetes cases that were "diabetes with circulatory complication" or "uncomplicated diabetes" were recoded.…”
Section: Comparison With the Literaturesupporting
confidence: 88%
“…Unfortunately, we do not have data on specific causes of deaths. Nevertheless, identification of causes of death is not free of problems [17][18][19][20][21]; for example, sudden cardiac death prevalence was found to be overestimated by 47% [22] and use of all-cause mortality as an unbiased endpoint was advocated [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests the underestimation of specific causes of death that are of particular importance to individuals with diabetes, such as acute complications and CVD, when using death certificates as the only source of information. Other studies have also underscored the problem with the insufficient reliability of causes of death in type 1 diabetes when only considering death certificates (39,42,43). An important limitation of this study is that we did not have complete information on HbA 1c or smoking status, among other risk factors.…”
Section: Discussionmentioning
confidence: 99%